Changes in HCMV immune cell frequency and phenotype are associated with chronic lung allograft dysfunction - Rousselière, Amélie; Delbos, Laurence; Foureau, Aurore; Reynaud-Gaubert, Martine; Roux, Antoine; Demant, Xavier; Le Pavec, Jérôme; Kessler, Romain; Mornex, Jean-François; Messika, Jonathan; Falque, Loïc; Le Borgne, Aurélie; et al. (Frontiers in Immunology, 2023)
BACKGROUND. Human cytomegalovirus (HCMV) infection is common and often severe in lung transplant recipients (LTR); it is a risk factor associated with chronic lung allograft dysfunction (CLAD). The complexe interplay between HCMV and allograft rejection is still unclear. Currently, no treatment is available to reverse CLAD after diagnosis and the identification of reliable biomarkers that can predict early development of CLAD is needed. This study investigated the HCMV immunity in LTR who will develop a CLAD. METHODS. This study quantified and phenotyped conventional (HLA-A2pp65) and HLA-E-restricted (HLA-EUL40) anti-HCMV CD8+T (CD8T) cell responses induced by infection in LTR developing CLAD or maintaining a stable allograft. The homeostasis of immune subsets (B, CD4T, CD8T, NK and γδT cells) post-primary infection associated with CLAD was also investigated. RESULTS. At M18 post-transplantation, HLA-EUL40 CD8T responses were less frequently found in of HCMV+ LTR (21.7%) developing CLAD (CLAD) than in LTR (55%) keeping a functional graft (STABLE). In contrast, HLA-A2pp65 CD8T were equally detected in 45% of STABLE and 47.8% of CLAD LTR. The frequency of HLA-EUL40 and HLA-A2pp65 CD8T among blood CD8T shows lower median values in CLAD LTR. Immunophenotype reveals an altered expression profile for HLA-EUL40 CD8T in CLAD patients with a decreased expression for CD56 and the acquisition of PD-1. In STABLE LTR, HCMV primary infection causes a decrease in B cells and an inflation of CD8T, CD57+/NKG2C+NK and δ2-γδT cells. In CLAD LTR, regulation of B, total CD8T and δ2+γδT cells is maintained but total NK, CD57+/NKG2C+NK and δ2-γδT subsets are markedly reduced while CD57 is overexpressed across T lymphocytes. CONCLUSIONS. CLAD associates with significant changes in anti-HCMV immune cell responses. Our findings propose that the presence of dysfunctional HCMV-specific HLA-E-restricted CD8T cells together with post-infection changes in the immune cell distibution affecting NK and γδT cells define an early immune signature for CLAD in HCMV+ LTR. Such a signature may be of interest for the monitoring of LTR and may allow an early stratification of LTR at risk of CLAD.